The Influence of Traumatic Axonal Injury in Thalamus and Brainstem on Level of Consciousness at Scene or Admission: A Clinical Magnetic Resonance Imaging Study - Moe, Hans Kristian (J Neurotrauma, 2018)
The aim of this study was to investigate how traumatic axonal injury (TAI) lesions in the thalamus, basal ganglia, and brainstem on clinical brain magnetic resonance imaging (MRI) are associated with level of consciousness in the acute phase in patients with moderate to severe traumatic brain injury (TBI). There were 158 patients with moderate to severe TBI (7–70 years) with early 1.5T MRI (median 7 days, range 0–35) without mass lesion included prospectively. Glasgow Coma Scale (GCS) scores were registered before intubation or at admission. The TAI lesions were identified in T2*gradient echo, fluid attenuated inversion recovery, and diffusion weighted imaging scans. In addition to registering TAI lesions in hemispheric white matter and the corpus callosum, TAI lesions in the thalamus, basal ganglia, and brainstem were classified as uni- or bilateral. Twenty percent of patients had TAI lesions in the thalamus (7% bilateral), 18% in basal ganglia (2% bilateral), and 29% in the brainstem (9% bilateral). One of 26 bilateral lesions in the thalamus or brainstem was found on computed tomography. The GCS scores were lower in patients with bilateral lesions in the thalamus (median four) and brainstem (median five) than in those with corresponding unilateral lesions (median six and eight, p = 0.002 and 0.022). The TAI locations most associated with low GCS scores in univariable ordinal regression analyses were bilateral TAI lesions in the thalamus (odds ratio [OR] 35.8; confidence interval [CI: 10.5−121.8], p < 0.001), followed by bilateral lesions in basal ganglia (OR 13.1 [CI: 2.0–88.2], p = 0.008) and bilateral lesions in the brainstem (OR 11.4 [CI: 4.0–32.2], p < 0.001). This Trondheim TBI study showed that patients with bilateral TAI lesions in the thalamus, basal ganglia, or brainstem had particularly low consciousness at admission. We suggest these bilateral lesions should be evaluated further as possible biomarkers in a new TAI-MRI classification as a worst grade, because they could explain low consciousness in patients without mass lesions.